Correlação entre hiperlipidemia e endocrinopatias em uma população de cães de Campo Grande, Mato Grosso do Sul - Beatriz Crepaldi Alessio (2022)
Hyperlipidemia is defined as the increase in serum concentrations of cholesterol and/or triglycerides, having as a cause endocrinopathies such as hypothyroidism, diabetes mellitus and hypercortisolism, in addition to pancreatitis and obesity and liver diseases. Severe hyperlipidemia leads to problems such as atherosclerosis, neuropathies, ocular and hepatobiliary changes, in addition to the predisposition to pancreatitis. The present study evaluated 217 dogs treated at the specialized endocrinology service in Campo Grande, State, Brazil, of which 146 had a concluded diagnosis of at least one endocrinopathy. Hyperadrenocorticism was confirmed in 75.34% (110/146), 10.95% (16/146) were hypothyroid and 104 animals were classified as obese (71.23%). Diabetes was identified in 13.69% (20/146) of the animals, and of these three had associated hypoadrenocorticism. Regarding hyperlipidemia, 71.88% (156/217) of the dogs evaluated presented alterations in lipid metabolism, and 55.12% (86/156) had hypercholesterolemia and 86.53% (135/156) hypertriglyceridemia. Of the 156 hyperlipemic individuals, 55.12% (86/156) were diagnosed with hyperadrenocorticism, 6.41% (10/156) with diabetes, 1.28% (2/156) with diabetes and hyperadrenocorticism, and 7.05% (11/156) with hypothyroidism. Regarding obesity, 78 animals (50%) presented hyperlipidemia.